The impact of organizational factors on lecturer engagement in private universities of economics in Vietnam - Nguyen Thi Ly (Journal of State Management, 2025)
Vietnam's higher education system is experiencing significant movement toward greater autonomy, increased competition, and deeper integration. Amidst these developments, private universities in Hanoi specializing in economics are encountering growing challenges in recruiting and retaining qualified, committed faculty members. Fluctuations in human resources across institutional levels have highlighted the urgent need to identify determinants of lecturer engagement. This study uses Structural Equation Modeling (SEM) to analyze empirical findings across five categories of organizational factors: organizational culture, leadership capacity, compensation and benefits, opportunities for training and advancement, and university social responsibility. Drawing on these results, the article offers several policy recommendations designed to strengthen lecturer engagement within private economics universities in Hanoi, thereby supporting educational quality and promoting sustainable growth in an increasingly competitive landscape.